Pengelolaan Sampah Pasar Tradisional di Pedesaan Indonesia - Pangesti, Devy Ega; Wijayanti, Yuni (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Urban waste in Indonesia comes from traditional markets, the volume of waste is increasing every year. This study aims to determine the factors that influence the management of traditional market waste in Pucung Rejo Village. Method: quantitative analysis with cross sectional approach. The population is all traditional market traders in Pucung Rejo Village. The sample in the study was 74 respondents. The sampling technique was simple random sampling. The instrument uses observation sheets and questionnaires. Data obtained from primary data and secondary data. The data were analyzed using the chi square test with the help of SPSS version 22.0. Results: bivariate analysis with Chi Square test was knowledge p = 0.000, OR 2.6 (95% CL = 1.681-4.170), attitude p = 0.000, OR 2.6 (95% CL = 1.617 - 4.373) waste disposal facilities p = 0.024, OR = 1.8 (95% CL = 1.075 – 3.168). So that there is an influence between knowledge, attitudes and waste disposal facilities on traditional market waste management in Pucung Rejo Village. By providing information about waste management, supervising market traders and fulfilling waste disposal facilities, it is very necessary. Conclusion: it is necessary to empower market traders by market managers regarding waste management.